Pengaruh Komunikasi dan Lingkungan Kerja terhadap Prestasi Kerja Pegawai Rumah Sakit Umum BHAKTI RAHAYU Tabanan - Ni Putu Vera Yanti; I Made Sunata; I Putu Agus Suarsana Ariesta (Journal Research of Management, 2024)
Work performance is something that needs to be considered in a company, because the better employee performance can have an impact on the success of a company. The problems raised in this study are whether communication (X1) affects employee performance (Y) at Bhakti Rahayu Tabanan General Hospital, does the work environment (X2) affect employee performance (Y) at Bhakti Rahayu General Hospital Tabanan, how much influence does communication and work environment have on employee performance at Bhakti Rahayu Tabanan General Hospital and which independent variables have a dominant influence on employee performance at Bhakti Rahayu Tabanan General Hospital. The population in this study amounted to 76 people. This study uses the population as a sample. The data analysis technique used is descriptive analysis, data quality test, classical assumption test, multiple linear regression analysis, t-test analysis, and determination analysis. The results of the analysis show the regression model Y = 1.309 + 0.257 (X1) + 0.564 (X2). The conclusion obtained is that communication (X1) partially has a positive and significant effect on employee performance (Y) at Bhakti Rahayu Tabanan General Hospital as indicated by the regression coefficient b1X1 which is positive. The work environment (X2) partially has a positive and significant influence on employee performance (Y) at Bhakti Rahayu Tabanan General Hospital, this can be seen in the b2X2 coefficient which is positive. The magnitude of the influence of communication and work environment on employee performance at Bhakti Rahayu Tabanan General Hospital is 64.8% and the remaining 35.2% is influenced by other variables not examined in this study. The independent variable that has a dominant influence on employee performance can be seen in the value of Standardized Coefficients Beta, namely the communication variable (X1), which is equal to 0.257, while the work environment variable (X2) is equal to 0.564.